Training Documentalists in the Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
training courses on sources of agricultural information. In 1988 the third course took place in the Caribbean, in conjunction with CARDI (the Caribbean Agricultural Research and Development Institute), in Trinidad November 21 to December 3